An optimal (S-1, S) inventory control policy for multi-indentured aircraft engine spare parts - Ang, Eugene Zheng Hao (2010)
This paper presents a mathematical model for determining optimal stock levels of a three-level indentured aircraft engine comprising modules and components. The mathematical model follows an (S-1, S) inventory control policy typically used for high cost, low demand repairable items. A (S-1, S) policy means that the reorder point is S-1, quantity of order is 1 and stock level is a decision variable to be determined. The application of this model is targeted at air transport companies that own these spares, with the aim of reducing their costs of spares.